2018
DOI: 10.1038/s41598-018-34731-x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the immune microenvironment of a tissue by digital imaging and cognition network

Abstract: Evidence has highlighted the importance of immune cells in various gut disorders. Both the quantification and localization of these cells are essential to the understanding of the complex mechanisms implicated in these pathologies. Even if quantification can be assessed (e.g., by flow cytometry), simultaneous cell localization and quantification of whole tissues remains technically challenging. Here, we describe the use of a computer learning-based algorithm created in the Tissue Studio interface that allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Each slide was automatically analyzed by a specific DIA algorithm developed for our study that was based on Definiens Cognition Network Technology®. All steps and settings have been previously detailed (see Supporting Information for all full detailed protocol) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each slide was automatically analyzed by a specific DIA algorithm developed for our study that was based on Definiens Cognition Network Technology®. All steps and settings have been previously detailed (see Supporting Information for all full detailed protocol) …”
Section: Methodsmentioning
confidence: 99%
“…All steps and settings have been previously detailed (see Supporting Information for all full detailed protocol). 38…”
Section: Immunofluorescent Staining and Quantification Of Immune Cellmentioning
confidence: 99%
“… 51 Inflammation and immune cell markers are unquestionably among the most useful biomarkers of efficacy and many researchers have developed image analysis algorithms to study immune infiltration in mouse models of colitis, 42 asthma, 52 and cancer. 53 …”
Section: Applications Of Biomarker Imaging Analysismentioning
confidence: 99%
“…Fluorescent probes have also been designed to investigate the accumulation of hyaluronan and collagen in ex vivo tumor sections [335] and for in vivo intraoperative imaging of hyaluronic acid conjugates for assistance in surgical resection of pancreatic cancer [336] . Both MSCs and immune cells may be labeled ex vivo with fluorescent molecules to determine the localization and quantification of immune cells in whole tissue [337] or to inject the prelabeled cells and view their activity in vivo [338,339] . Quante et al [340] showed evidence that CAFs originate from bone marrow and derive from MSCs through the expression of red fluorescent protein in aSMA-RFP transgenic mice.…”
Section: Fluorescence Imagingmentioning
confidence: 99%